Production of dried tomato powder with a high concentration of functional components and nutrients - Masayo Nishizono; Cinthya Soreli Castro Issasi; Jonas Karl Christopher N. Agutaya; Mitsuru Sasaki; Hiroyuki Mizukami (Journal of Antioxidant Activity, 2023)
The use of conventional drying methods for dehydrating vegetables and fruits with high sugar, amino acid, and moisture content is not feasible. Under extreme conditions, drying reduces the amount of functional ingredients present in these vegetables and fruits. Recently, there has been an increasing demand for powdered tomatoes because of their nutritional and functional components. This study aimed to evaluate tomato drying under normal pressure and low-temperature conditions, to efficiently reduce water content without compromising on product quality. A convection dryer, most widely used in food factories, was used in this study. This equipment uses a low temperature zone not normally used for drying, and processes the raw material to increase the drying area for rapid drying. The proposed method was validated by comparing the moisture and functional component contents, and the antioxidant activity of the dried product with those of the dried product obtained via freeze-drying. The results suggest that the proposed low-temperature drying method can produce functional dried food at food processing sites faster than using freeze-drying, with a residual rate of functional ingredients exceeding 90 %. Thus, low-temperature drying can be used as a simple and cost-effective method for the production of uniform dry tomato powder.
Keywords: freeze-drying